Mobile Network Operators' Business Risks in Next-Generation Public Safety Services - Tapio Savunen; Pekka Kekolahti; Petri Mähönen; Heikki Hämmäinen; Kalevi Kilkki (International Telecommunications Society (ITS), 2023)
Field of research - This research is in the field of public safety communications in mobile broadband 4G/5G networks. Its specific focus is mobile network operators and their business risks in the public safety market. Purpose - This research is intended to provide a qualitative model of MNOs' business risks in the public safety business. The risk assessment covers the business model used in European public safety mobile broadband projects, which is used in three of five ongoing projects. Methods and data - A qualitative method was used for the current research. The risk model is an influence diagram, which is a directed graph consisting of nodes and arcs. The risk model uses the causal taxonomy of risk, which is commonly used for qualitative and quantitative causal models based on Bayesian networks. An expert panel and the Delphi method were used to create the risk model. The expert panel's risk assessment was conducted using a case study that followed the model of European public safety projects. Findings - The risk model shows that business risks are a threat to the financial goals of MNOs' public safety business. The potential consequences of the risks are additional costs, contractual penalties, and lost service revenue. They can also have a negative impact on the MNO''s regular business, which in the worst case can lead to a loss of market share and revenue. All of these have a negative impact on the MNOs' financial results. Value - This research brings new knowledge about MNOs' business risks in next-generation public safety services. Procurement authorities can use the results when planning public procurements in the field of mobile broadband public safety services. MNOs can benefit from these results by gaining a better understanding of potential risks, their consequences, and their control and mitigation in public safety projects.
Keywords: 330; mobile network operator; public safety; business risk; risk model; mobile broadband